A Prática Desportiva e o Rendimento Académico... Que relação? Um estudo realizado com alunos do 3º Ciclo do Ensino Básico - Diogo Sobreiro Ribeiro (2017)
Being Sport one of the resources that humanity has related to the development of young people it is essential that society exploits the benefits that Sports Practice brings so research in the last decades showed the advantages of Sports Practice near different populations but this association between Sports and Academic Performance is not clear and sometimes seems to be contradictory. In this study we had as main goals: to analyze in adolescents of the 3rd level in Elementary Education and verifying the differences according to sex and age: i) Sports Practice outside school; ii) the relationship between Sports Practice and Academic Performance, considering the number of retentions and average in both levels of education. The study was conducted in schools in the north of Portugal with 1484 students (49.3% male and 50.7% female), with ages reached from 12 to 17 years (mean age 13.8 years old). The instrument used was the "Inventory of behaviors related to the health of adolescents" developed by (Corte-Real et al., 2004). We present as main results: a) 2/3 of the adolescents in the sample presented a regular Sports Practice (2 or more practices per week); b) male adolescents showed a greater tendency to Sports Practice when compared to female adolescents, being that these differences are statically significant; c) there were no statistically significant differences when we consider ages as variable; d) it was possible to observe that the most active boys and girls in the 2nd and 3rd level of Basic Education (5th, 6th, 7th, 8th, 9th grade) presented the best classifications, 77.5% of the girls and 59% of the boys didn't have retentions(being that the less active adolescents had a decrease to 23% boys and to 42% to girls). These results reinforce the need to work early with adolescents about the importance of Sports Practice and the possibility of integration sports and school ever since Academic Performance does not change, otherwise it can improve in many situations.